2021
DOI: 10.3390/ma14061570
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PVA/CeO2 Based Nanocomposites with Tuned Refractive Index and Reduced Absorption Edge: Structural and Optical Studies

Abstract: In the current study, polymer nanocomposites (NCPs) based on poly (vinyl alcohol) (PVA) with altered refractive index and absorption edge were synthesized by means of a solution cast technique. The characterization techniques of UV–Vis spectroscopy and XRD were used to inspect the structural and optical properties of the prepared films. The XRD patterns of the doped samples have shown clear amendments in the structural properties of the PVA host polymer. Various optical parameters were studied to get more insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…It is clear that n of the pristine PVA/G behaves quasi‐steady in the Vis–NIR spectra region, which is compatible with the reported findings. [ 37,73 ] While it is noticed that Fe 2 O 3 NPs filling has a pronounced effect on the refractive index of the host PVA/G matrix. Moreover at any certain incident wavelength λ , the refractive index of the NC film increases as the concentration of the nano fillers is increased up to 10 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that n of the pristine PVA/G behaves quasi‐steady in the Vis–NIR spectra region, which is compatible with the reported findings. [ 37,73 ] While it is noticed that Fe 2 O 3 NPs filling has a pronounced effect on the refractive index of the host PVA/G matrix. Moreover at any certain incident wavelength λ , the refractive index of the NC film increases as the concentration of the nano fillers is increased up to 10 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35 ] Also, the optical bandgap of Cu/MnS NPs filled PVA/PVP blend was explored by Heiba group. [ 36 ] Aziz et al [ 37 ] showed that tuning the refractive index and the absorption of PVA polymer could be achieved via filling with CeO 2 NPs. The photoluminescence and electrical properties of PVA polymer were tuned via filling with Ag 2 S NPs by Al‐Harthi et al [ 11 ] Taha and Alzara explored the dielectric and thermal behavior of PVA filled with SrTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 47 ] Dispersion energy E d gives the normal electronic excitation spectrum and measures a mean strength of inter band transitions which was described by the charge distribution within unit cell whereas Oscillator energy E o estimates mean energy gap between centers of valence band and conduction band (direct bandgap). [ 48,49 ] Refractive index was associated with photon energy hν by an empirical equation:n2=1+EoEdEo2(hν)2…”
Section: Resultsmentioning
confidence: 99%
“…The refractive index and its dispersion behavior are among the key optical material properties to be studied. The refractive index dispersion is crucial in evaluating the optical communication for spectral dispersion [ 105 ].…”
Section: Resultsmentioning
confidence: 99%